Roles of Village Stakeholders on Immunization Program during Pandemic Outbreak in Central Java, Indonesia - Ayun Sriatmi; Sutopo Patria Jati; Wulan Kusumastuti (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Tegal district is facing obstacles in achieving immunization targets during the Covid-19 pandemic as the declining number of children who have been immunized. The role and support of village stakeholders considerably play a very significant role in overcoming these obstacles. This current study aimed to analyze the dimensions of village stakeholders’ roles in achieving basic immunization targets during the pandemic era. This study was conducted using a quantitative survey with a cross-sectional approach. The participants were all village stakeholders related to the immunization program. There were 300 people from 30 selected villages as samples chosen through a purposive technique sampling. The roles of stakeholders were found to be the dimensions of perceptions, powers, and respectively interests. The results were most of the stakeholders showed such positive dimensions of perception related to their roles in immunization as well as interest dimensions. All respondents, in addition, considered that their institutions have no power in implementing immunization programs in villages. The immunization success was the responsibility of PHC and health workers instead. There was a relationship between perceptions with strengths and interests, as well as a relationship between strengths with interests of village stakeholders in the immunization program (p<0.05). The weakest role of village stakeholders was in the power dimension as they rely highly on the local governments and health workers with a weak authority to make decisions. Thus, strengthening the role needs to be done through continuous socialization and dissemination with interactive coordination methods, and direct and personal communication.